STRATEGI KOMISI PEMILIHAN UMUM KOTA SEMARANG DALAM MENSOSIALISASIKAN PEMILIHAN WALIKOTA 2015 - saputra, tiko wicaksono; ., fitriyah; astrika, lusia (Journal of Politic and Government Studies, 2016)
Abstract Elections are one indicator of democracy, where the people directly involved in determining the direction and policy leaders and state politics for the next five years. But this time they found the lowest participation rate caused by several factors: a decrease in the level of confidence in the behavior of the corrupt political elites, factors critical meaning critical community can analyze the results of the previous general election in realizing the promise during the campaign, a factor the circumstances in which the person does not may vote at the polling station where he lived because the person registered at the polling station other areas eg people who wander, lack of socialization election by the general elections Institute so that people do not know how big the benefits of involvement in the election itself, the lack of role of political parties in political socialization. Of these factors, the Election Commission of Semarang had planned strategies such as long-term evaluation. In 2015 came the idea and creation to increase political participation as student council president election held in SMA / SMK / MA as the city of Semarang. Then with Effectyang Multiple factors together with the first simultaneous elections or through Parliament as the previous year which caused controversy. The controversy is being used for public communication. After seeing the condition as a way strategy, the State Election Commission conducted a survey with academics that Cepp UNDIP to make an assessment of the participation of local elections of 2015. According to this problem, the need for research to analyze and assess socialization Semarang State Election Commission by way of strategy Keywords: Elections, Democracy, Strategy, socialization, and socialization, Participation, Public Communication